The SIRD epidemiological model applied to spread of the COVID-19 in the Peruvian región of Tacna - Vargas-Pichón, Humberto B. (2022)
In the present research, the epidemiological model SIRD was used to study the spreed of the COVID-19 Pandemic in the Tacna Region. To determine the parameters of the model, the information published through social networks by the Regional Health Directorate of the Tacna Region of Peru was used, which was systematized in an EXCEL matrix and then exported to process the information in the System of Scientific Computing Mathematica. As a result, the graphs corresponding to the model referred to the Susceptible, Infected, Recovered and Deceased individuals from the COVID-19 Pandemic in the Tacna Region were obtained and then the graphs were interpreted in the time interval of the study. Keywords: COVID-19, SIRD epidemiologic model.